A Critical Look at Measures of Macroeconomic Uncertainty - David Kjellberg; Erik Post (Uppsala University, Department of Economics, 2007)
This paper takes a critical look at available proxies of uncertainty. Two questions are adressed: (i) How do we evaluate proxies given that subjective uncertainty is inherently unobservable? (ii) Is there such a thing as a general macroeconomic uncertainty? Using correlations, some narrative evidence and a factor analysis we find that disagreement and stock market volatility proxies seem to be valid measures of uncertainty whereas probability forecast measures are not. This result is reinforced when we use our proxies in standard macroeconomic applications where uncertainty is supposed to matter. Uncertainty is positively correlated with the absolute value of the GDP-gap.
urn:nbn:se:uu:diva-10178
Keywords: C42; C82; 330; Uncertainty; Macroeconomics; Survey Data; Volkswirtschaft; Unvollkommene Information; Messung; Aktienmarkt; Volatilität; VAR-Modell